Cognitive and emotional processes in Web-based education : integrating human factors and personalization - Mourlas, Constantions; Tsianos, Nikos; Germanakos, Panagiotis (Hershey : Information Science Reference, 2009)
Summary: "This book ressents theories and practical frameworks to asist educators and trainers in developing e-learning applications"- provided by publisher.
Includes bibliographical references and index
Keywords: Web-based instruction; Individualized instruction; Emotions and cognition; Cognitive styles